KAJIAN PARIBASA BALI DALAM PUPULAN SATUA BALI ANYAR "BEGAL" - Ni Wayan Apriani (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
This study aimed at describing the types and functions of Balinese proverb contained in the reflection of pupulan satua Bali Anyar "Begal" by IDK Raka Kusuma. Data collection was carried out using document study and interview techniques. Then the data collected was analyzed using qualitative descriptive analysis techniques using the Miles and Huberman analysis models. The results of this study indicated that there were three types of Balinese proverbs used in the text, namely sesawangan, sesonggan and papindan. While the function of Balinese proverb in the text, among others, was to describe the situation, as a satire and as a compliment.Keyword: proverb, Pupulan satua Bali Anyar "Begal"